La protección administrativa y judicial de los bienes públicos en Colombia. Dificultades, incoherencias y perspectivas - Pimiento Echeverri, Julián Andrés (2019)
The protection —judicial or administrative— of public assets is a Constitutionalimperative. In order to fulfill that mandate, it is necessary to draw a proper diagnoseof the tools public administrations have to protect those assets, specially we mustestablish the adequate way to use those tools to maximize their public use; however,as a consequence of that diagnosis the entire regulation of public properties should beupdated, so it responds to the constitutional imperative.